Handbook of research on new challenges and global outlooks in financial risk management - Madaleno, Mara, 1981-; Vieira, Elisabete S.; Barbuta-Misu, Nicoleta, 1978- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book discusses the financial instruments firms use to manage the different kind of financial risks, such as interest rate risk, corporate risk, credit risk, liquidity and default risk and is intended to help the reader understand the risk management practices in different countries, and their relationship to firms' performance, and other dimensions of companies"--